Biological response of maize hybrids to simulated drift of glyphosate - Dudić, Milica (Acta herbologica, 2021)
The effect of simulated glyphosate drift on six maize hybrids (NS 6102, AS 334, Lucius, Confites, DKC 5031 and P0216) was investigated in Kulpin during vegetation season in 2018. Glyphosate was applied twice, in stages 3-4 and 6-7 of fully formed maize leaves, with five different sublethal doses of herbicide: 10, 20, 40, 80, 160 g/ha. Phytotoxicity assessments of glyphosate were performed 7, 14, and 21 days after herbicide application. Analysis of the results showed that glyphosate in an amount of 160 g/ha in phase 3-4 maize leaves, caused easier damage, without affecting the height and grain yield, while phytotoxicity was not observed at lower applied amounts. Significant phytotoxicity on maize plants in the form of chlorosis, leaf curling and notable necrotic area was found at application of glyphosate in an amount of 160 g/ha in the phase of 6-7 leaves. Maize hybrids in this treatment achieved an average of 81% lower yield compared to control. Hybrids treated with an amount of 80 g/ha of glyphosate had a reduced yield by 30%, while in other lower amounts the reduction in yield was ranged from 25 to 18% compared to the control.